The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s10198-016-0813-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact assessment of a pay-for-performance program on breast cancer screening in France using micro data

Abstract: The French P4P program had a nonsignificant impact on breast cancer screening uptake. This result may reflect the fact that the low-powered incentives implemented in France through the CAPI might not provide sufficient leverage to generate better practices, thus inviting regulators to seek additional tools beyond P4P in the field of prevention and screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Four studies were executed in the US, with their focus varying from publicly funded safety-net community health centers ( 30 ), Medicaid-focused managed care ( 26 ), a commercial health plan ( 23 ) to a cross-sector study ( 45 ). Two studies in a country with a Bismarck model: one in Estonia ( 42 ) and one in France ( 49 ). One study was executed in Mozambique and concerned a donor-sponsored program ( 47 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies were executed in the US, with their focus varying from publicly funded safety-net community health centers ( 30 ), Medicaid-focused managed care ( 26 ), a commercial health plan ( 23 ) to a cross-sector study ( 45 ). Two studies in a country with a Bismarck model: one in Estonia ( 42 ) and one in France ( 49 ). One study was executed in Mozambique and concerned a donor-sponsored program ( 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…As presented in Table 1 , a total of 20 studies focus on the relationship between P4P bonuses and prevention ( 23 , 24 , 26 , 28 , 30 32 , 34 , 35 , 37 40 , 42 – 44 , 46 49 ). Seven papers study P4P incentives awarded at practice level ( 26 , 28 , 34 , 39 , 43 , 47 , 48 ), from which four studies pertain to the Quality and Outcome Framework (QOF) P4P program in the UK, where incentives represent up to 25% of annual income ( 34 , 39 , 43 , 48 ).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of program impact on quality measures 22 (39%) (CHAUDHURI et al, 2016), (KRISTENSEN et al, 2014), (GILLAM; SIRIWARDENA; STEEL, 2012), (JHA et al, 2012), (WERNER et al, 2011), (SICSIC;FRANC, 2017), (JU KIM et al, 2017), (ANGIER et al, 2017), (COX et al, 2016), (ROSENTHAL et al, 2016), (MICHEL-LEPAGE; VENTELOU, 2016), (CHI et al, 2016), (POLI NETO et al, 2016), (DAS; GOPALAN; CHANDRAMOHAN, 2016), (WU et al, 2016), (GLEESON; KELLEHER; GARDNER, 2016), (CHEN;CHENG, 2016), (BASTIAN et al, 2016a), (ELLIOTT et al, 2016b), (CHAUDHURI et al, 2016), (BASTIAN et al, 2016b), (MURPHY et al, 2016) Descriptive analysis, advantages and disadvantages and points of attention 13 (23%) (FROIMSON et al, 2013b), (EIJKENAAR, 2013), (VAN HERCK et al, 2010a), (CARLSON et al, 2010), (ELBULUK;O'NEILL, 2017), (MILLER et al, 2017), (TABRIZI et al, 2017), (ANOUSHIRAVANI; IORIO, 2016), (CHEE et al, 2016), (KRETZSCHMAR et al, 2016), (KONDO et al, 2016) By arranging the articles by similarity of themes, as shown in table 3, it was observed that most of the studies analyzed (39%) evaluate the impact of performance-related pay programs on quality indicators. These studies generally make comparisons of groups under incentive influence against control groups without the incentive, comparing indicators before and after program implementation.…”
Section: Referencesmentioning
confidence: 99%
“…After its introduction,other countries worldwide, such as France [18,19], Estonia [20] and Taiwan [21,22] started a P4P quality system for GPs to reward excellent outcomes. Despite the efforts, the spread of these programmes in Europe is still limited.…”
Section: Introductionmentioning
confidence: 99%